Compensation in the isopropyl alcohol dehydration over sol–gel Al2O3–TiO2 oxides: Effect of calcining temperature. (1st June 2015) - Escobar, J.; De Los Reyes, J.A.; Viveros, T.; Valle-Orta, M.; Barrera, M.C.
Graphical abstract: Highlights: Sol–gel alumina, titania and mixed oxides (Al/Ti = 2 and 25) tested in isopropanol dehydration. Alumina and titania had the highest specific and intrinsic activity, respectively, in isopropanol dehydration. Compensation effects observed in isopropanol dehydration over alumina-containing materials. Isokinetic temperatures determined for alumina and mixed oxides (Al/Ti = 2 and 25). Abstract: Compensation effects were found in isopropanol dehydration over alumina (A), titania (T) and corresponding mixed oxides (Al/Ti = 2 and 25 mol ratio, AT2 and AT25, respectively) synthesized by low-temperature sol–gel. Prepared materials (calcined in the 573–1173 K) range were characterized by several techniques (N2 physisorption, XRD, thermal analysis and SEM). In general, Al2 O3 had the highest reaction rate (at 473 K) in propylene formation meanwhile both mixed oxides had much lower activity. TiO2 had minimal dehydrating activity that, nevertheless, was the highest intrinsic one (in areal basis). Constable plots were obtained for materials annealed at various temperatures, but for titania series. A clear isokinetic temperature ( Tθ ) was observed for alumina series whereas for AT25 materials, a Tθ pole was registered but for the sample calcined at the most severe condition. Meanwhile, two Tθ poles were identified for AT2 solids, the first one corresponding to materials calcined at moderate temperature whereas the other set apart solids annealed under severe conditions. As expected, no isokinetic temperature was observed in Arrhenius plots corresponding to alcohol dehydration over TiO2 materials.